Developmental associations between bullying victimization and suicidal ideation and direct self‐injurious behavior in adolescence and emerging adulthood. (30th September 2021) - Zhu, Xinxin; Griffiths, Helen; Eisner, Manuel; Hepp, Urs; Ribeaud, Denis; Murray, Aja Louise
Abstract : Background: Bullying, suicide, and self‐injury are significant issues among young people. Extensive research has documented bullying victimization associations with suicidal ideation and self‐injury; however, the modeling approaches used have mostly not addressed the relations between these constructs at the within‐person level, and it is these links that are critical for testing developmental theories and guiding intervention efforts. This examined the within‐person, bidirectional relations between these constructs in adolescence and emerging adulthood. Methods: Participants were from the Zurich Project on Social Development from Childhood to Adulthood (z‐proso). Random intercept cross‐lagged panel models (RI‐CLPMs) were fit to general and sexual bullying victimization and suicidal ideation data at ages 15, 17, and 20 ( n = 1465), and general and sexual victimization and direct self‐injurious behavior data at ages 13, 15, 17, and 20 ( n = 1482). Results: There was a positive within‐person effect of age 15 general bullying victimization on age 17 suicidal ideation (β = .10) and age 17 suicidal ideation on age 20 general bullying victimization (β = .14). Conclusions: General bullying victimization and suicidal ideation may have detrimental effects on each other over development but at different stages.